Engineering the Site‐Disorder and Lithium Distribution in the Lithium Superionic Argyrodite Li6PS5Br. Issue 5 (28th December 2020) - Gautam, Ajay; Sadowski, Marcel; Ghidiu, Michael; Minafra, Nicolò; Senyshyn, Anatoliy; Albe, Karsten; Zeier, Wolfgang G.
Abstract: Lithium argyrodite superionic conductors, of the form Li6 PS5 X (X = Cl, Br, and I), have shown great promise as electrolytes for all‐solid‐state batteries because of their high ionic conductivity and processability. The ionic conductivity of these materials is highly influenced by the structural disorder of S 2− /X − anions; however, it is unclear if and how this affects the Li distribution and how it relates to transport, which is critical for improving conductivities. Here it is shown that the site‐disorder once thought to be inherent to given compositions can be carefully controlled in Li6 PS5 Br by tuning synthesis conditions. The site‐disorder increases with temperature and can be "frozen" in. Neutron diffraction shows this phenomenon to affect the Li + substructure by decreasing the jump distance between so‐called "cages" of clustered Li + ions; expansion of these cages makes a more interconnected pathway for Li + diffusion, thereby increasing ionic conductivity. Additionally, ab initio molecular dynamics simulations provide Li + diffusion coefficients and time‐averaged radial distribution functions as a function of the site‐disorder, corroborating the experimental results on Li + distribution and transport. These approaches of modulating the Li + substructure can be considered essential for the design and optimization of argyrodites and may be extended to other lithium superionic conductors. Abstract : The site‐disorder can be carefully controlled in Li6 PS5 Br by tuning the synthesis conditions; different degrees of site‐disorder are achieved from 10% to 39% of S 2− on the Br − site. The combination of neutron diffraction and simulations show that the changing site‐disorder affects the local charge homogeneity, which in turn directly affects the lithium distribution and ionic conductivity.